Text2Quit: an analysis of participant engagement in the mobile smoking cessation program. (3rd July 2016) - Heminger, Christina L.; Boal, Ashley L.; Zumer, Maria; Abroms, Lorien C.
ABSTRACT: Background : Text2Quit, an interactive text-messaging program aimed at smoking cessation, has been shown to increase quit rates, but engagement has not been thoroughly explored. Understanding the program features associated with engagement and behavior change is integral for effective program design. Objectives : This study explored participants' interaction with the Text2Quit text-messaging program and associations between engagement and smoking cessation. Methods : The study included the 262 participants who received the Text2Quit intervention. Self-reported engagement measures, primarily usage of Text2Quit keywords and survey responses, were collected through computer records of participant use. Demographic variables and self-reported smoking abstinence were recorded in surveys at baseline and 6-month assessment. Results : The majority of participants (73%) maintained their subscription during the 6-month intervention. On average, participants received 210.51 text messages, 23.75 emails, and logged into the web portal 1.94 times. Being female was predictive of engagement with the program ( β = 15.39). Program engagement, measured by the keyword PLEDGE ( p = .002) and the Smokefree Status at 7 Days survey ( p < .001) were associated with 6-month abstinence; use of keywords SMOKED ( p < .001), RELAPSE ( p = .007), and STOP ( p = .023) were inversely related to abstinence. While abstainers ( N = 83, 31%) stayed enrolled longer and engaged with the program more frequently, program "dose" was not predictive of smoking cessation. Conclusions : Using interactive tools such as pledges and reporting on smoking status were predictive of cessation. Further study of program features is required to understand how to optimally design text messaging programs.